2021
DOI: 10.1111/tpj.15106
|View full text |Cite
|
Sign up to set email alerts
|

RAB GTPASE HOMOLOG 8D is required for the maintenance of both the root stem cell niche and the meristem

Abstract: Previous studies have suggested that the plastid translation elongation factor, elongation factor thermo unstable (EF-Tu), encoded by RAB GTPASE HOMOLOG 8D (RAB8D) is essential for plant growth. Here, through analyzing the root phenotypes of two knock-down alleles of RAB8D (rab8d-1 and rab8d-2), we further revealed a vital role for RAB8D in primary root development through the maintenance of both the stem cell niche (SCN) and the meristem. Our results showed that RAB8D deficiency affects the root auxin respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This opens the question on organ‐specific GUN1 function and the regulation of GUN1 degradation. Plastid retrograde signals have been shown to be active in roots, and at least the signals originated in response to defects in plastid translation are mediated by GUN1 and have effects on root development (Sullivan & Gray, 1999; Garnik et al ., 2019; Li et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This opens the question on organ‐specific GUN1 function and the regulation of GUN1 degradation. Plastid retrograde signals have been shown to be active in roots, and at least the signals originated in response to defects in plastid translation are mediated by GUN1 and have effects on root development (Sullivan & Gray, 1999; Garnik et al ., 2019; Li et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of the Arabidopsis GTPASE HOMOLOG 8D ( RAB8D ) gene, which encodes a plastid‐targeted counterpart of the prokaryotic translation elongation factor thermal unstable (EF‐Tu) and is required for the translation of proteins synthetized in the chloroplast, causes impaired chloroplast function, dramatically affecting meristem size and root growth. Genetic studies revealed that RAB8D deficiency activates the ATM–SOG1 module, which regulates SMR5 expression, being partly responsible for the root growth inhibition (Li et al., 2021). In addition, it has been reported that atm , atr , and sog1 mutant seedlings grown in the presence of ciprofloxacin, a genotoxin that specifically targets organellar DNA, are more severely affected than wild‐type plants.…”
Section: Ddr Connected To Organellesmentioning
confidence: 99%
“…In sorghum deep roots, SbATC could be involved in long-distance signaling to the shoot or regulation of root meristem interaction with FT-like peptides that modulate growth. The sorghum homolog of AtATM (Sobic.003G103701) that is differentially expressed in DR could be involved in root stem cell niche and meristem maintenance as occurs in Arabidopsis (Li et al, 2021). Sorghum homologs of bZIP29 (Sobic.007G182500), a regulator of root cell number (Van Leene et al, 2016;Wang et al, 2020), and ADA2B (Sobic.001G088100), a regulator of trichome density (Kotak et al, 2018) and growth (Rao & Virupapuram, 2021), could regulate root hair density or growth of deep roots.…”
Section: Genes Differentially Expressed In Deep Rootsmentioning
confidence: 99%